Midwives’ experiences of performing obstetric ultrasounds in antenatal care in eastern Ethiopia: Qualitative exploratory study - Maleda Tefera; Haymanot Mezmur; Mohammed Jemal; Nega Assefa (Women's Health, 2024)
Background: In 2016, the World Health Organization recommended inclusion of an ultrasound scan as part of routine antenatal care to improve pregnancy outcomes. However, most rural women in Ethiopia do not have access to ultrasound scanning as part of their routine antenatal care. Recently, ultrasonography services were introduced at health centers in Harar, Kersa, and Haramaya districts in Eastern Ethiopia. This expoloratory study aimed to examine experiences of pregnancy surveillance midwives in the Child Health and Mortality Prevention Surveillance (CHAMPS) who performed ultrasonography at health centers that are in the catchment area of Health and Demographic Surveillance Systems, in Eastern Ethiopia. Objective: To explor midwives’ experiences across 14 health centers in Eastern Ethiopia, located in the Kersa, Haramaya, and Harar Health and Demographic Surveillance Systems from February to April 2022 Design: Exploratory qualitative study. Methods: The methods used were based on the Standards for Reporting Qualitative Research framework. Purposeful sampling was used to explore experiences of midwives who performed ultrasonography at selected health centers. The Midwives are recurited, trained and stationed at the health ceners to do ultrasound scanning and other activities by the Child Helath and Mortality Prevention Surveillance (CHAMPS) pregancny surveillance activities. Among 17 midwives who had undergone ultrasonography training and who were actively involved in ultrasound scanning at health centers in Kersa, Haramaya, and Harar Health and Demographic Surveillance Systems, three midwives who worked at health centers with no power or near a hospital were excluded. Using tape recordings and note-taking, data were collected through in-depth interviews based on a semi-structured interview guide. Thematic analysis used for data categorization, and the trustworthiness of data was kept throughout the procedure using credibility, dependability, confirmability, and transferability. Results: In this study, we identified five main themes: Ultrasonography positively impacts midwives trained as sonographers; performing ultrasound scans enhances the skills and confidence of midwives, improving their professional development, Individual perception of self-efficacy; midwives’ belief in their abilities to perform ultrasound scans effectively influences their job satisfaction and motivation, Provision of care; integrating ultrasound into antenatal care enhances the quality, therapeutic communication, and personalized nature of care provided to pregnant women, Barriers to providing ultrasonography services; challenges such as shortage of ultrasonography-trained staff and workload can hinder the delivery of ultrasound services in rural areas, Community acceptance; the level of community understanding, trust, and support towards ultrasound technology and midwives as sonographers impacts the successful implementation and sustainability of ultrasound services. Conclusion: Ultrasonography performed by midwives at rural health centers had a considerable impact on antenatal care services and incareased confidence of midwives.